The Effect of Violation of the Rule Against Perpetuities in Missouri - Harry W. Kroeger (Washington University Law Quarterly, 1952)
It will suffice to observe at this point that there is a wide disposition among lawyers to conclude that in Missoui a limitation void for remoteness contaminates and renders void the entire property disposition of which the void limitation is part. That view is shared by that eminent authority on Missouri real property law, Mr. McCune Gill. It has undoubted pragmatic force because it is the governing principle for title examiners, under whose -scrutiny fall property dispositions far more numerous than those which come before the courts. Froni an equitable standpoint, there is little to commend such a concept of total invalidity.
Keywords: Perpetuities